2017
DOI: 10.1108/jfm-04-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement scale for facilities management service in Lagos-Nigeria

Abstract: Purpose Literature established that applicable parameters must be used in determining facilities management (FM) performance in any market; otherwise, findings could be confusing and misleading. This is particularly relevant to Nigeria where FM application is in its infancy and seriously constrained by particular socio-economic conditions which make it prone to crises situations such as frequent power outages and surges, abundance of fake and adulterated construction materials and equipment, heavy presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Ikediashi (2014) measured hospitals' FM services performance with four service quality attributes of service reliability, professionalism, responsiveness and competence. Related research by Koleoso et al (2017) within the Nigerian context developed 41 indicators classified under FM service quality, finance and disaster response. A review of healthcare facilities maintenance by Yousefli et al (2017) identified information technology and automated decision support systems as key indicators for facilities maintenance function and performance.…”
Section: Key Performance Indicatorsmentioning
confidence: 99%
“…Ikediashi (2014) measured hospitals' FM services performance with four service quality attributes of service reliability, professionalism, responsiveness and competence. Related research by Koleoso et al (2017) within the Nigerian context developed 41 indicators classified under FM service quality, finance and disaster response. A review of healthcare facilities maintenance by Yousefli et al (2017) identified information technology and automated decision support systems as key indicators for facilities maintenance function and performance.…”
Section: Key Performance Indicatorsmentioning
confidence: 99%
“…They define PM as “the process of quantifying the effectiveness and efficiency of an action.” The term effectiveness refers to the extent to which a particular requirement or goal is achieved, whereas efficiency indicates the speed of performing an action that by standards has to be both quantifiable and verifiable (Striteska and Spickova, 2012). In FM, PM could be viewed as a measure of how adequate FM is at identifying the needs of the users and its ability to put in place proper provisions to satisfy such needs and enhance their productivity (Koleoso et al , 2017). Congruence to this, Amaratunga and Baldry (2003) described PM as a process of assessing progress toward achieving pre-determined goals, including information on the efficiency by which resources are transformed into goods and services, the quality of these outputs and outcomes and the effectiveness of organizational objectives.…”
Section: Facilities Management Performance Measurementmentioning
confidence: 99%
“…According to Shohet (2003), such activities encompass the development of quantitative means to benchmark the performance and identify the strength and weakness for effective performance. The review shows that most of the maintenance performance indicators have been developed along the lines of functional, impact/physical, image, financial and quality measures (see Nik-Mat et al , 2011; Talib et al , 2013; Koleoso et al , 2017; Lavy et al , 2014a; Myeda et al , 2011). It is observed that most of the maintenance performance indicators by these authors are not quantified indicators and are largely generic.…”
Section: Hard Fm/facilities Maintenance Managementmentioning
confidence: 99%
“…Current FM practices are faced with numerous challenges. Prominent among them are reactive FM practices, lack of policy guidelines for FM, complete absence of building maintenance manuals, lack of funds, lack of strategic direction and socio-cultural issues (Koleoso et al, 2017). These challenges have created health-care healing environments which do not facilitate efficient health-care delivery thus allowing for the prevalence of hospitalacquired infections (Amankwah et al, 2019;Amos et al, 2020a).…”
Section: Health-care Facilities Management In Briefmentioning
confidence: 99%